2014
DOI: 10.1021/mp500367k
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of Ostwald Ripening in Low Molecular Weight Amino Lipid Nanoparticles for Systemic Delivery of siRNA Therapeutics

Abstract: Lipid nanoparticles (LNPs) represent the most clinically advanced technology for the systemic delivery of therapeutic siRNA in vivo. Toward this end, a novel class of LNPs comprising low molecular weight (MW) ionizable amino lipids having asymmetric architecture was recently reported.1 LNPs of these amino lipids, termed asymmetric LNPs, were shown to be highly efficacious and well tolerated in vivo; advances were enabled by improved endosomal escape, coupled with enhanced amino lipid metabolism and clearance. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 27 publications
(54 reference statements)
2
36
0
Order By: Relevance
“…EnCore A-C contains DL-036, which contains a dimethylglycine head group and two symmetrical acyl chains (Figure 2A). It has been previously suggested that incorporating asymmetric acyl chains into amino lipids can facilitate pH-dependent lipid phase transitions, thereby increasing endosomal release of the payload (3840). In a test set of otherwise identical LNPs, changing the lengths or the number of double bonds of one or both of the acyl chains significantly impacted the CTNNB1 mRNA silencing activity in tumors (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…EnCore A-C contains DL-036, which contains a dimethylglycine head group and two symmetrical acyl chains (Figure 2A). It has been previously suggested that incorporating asymmetric acyl chains into amino lipids can facilitate pH-dependent lipid phase transitions, thereby increasing endosomal release of the payload (3840). In a test set of otherwise identical LNPs, changing the lengths or the number of double bonds of one or both of the acyl chains significantly impacted the CTNNB1 mRNA silencing activity in tumors (Figure 2A).…”
Section: Resultsmentioning
confidence: 99%
“…Lipid Nanoparticles were prepared at Merck (West Point, PA, USA) and characterized as previously described [17,20]. The LNPs are comprised of an ionizable amino lipid ((13Z,16Z)- N , N -dimethyl-3-nonyldocosa-13,16-dien-1-amine), distearoylphosphatidylcholine (DSPC), cholesterol, and poly(ethylene glycol)2000-dimyristoylglycerol (PEG2000-DMG), in a molar ratio of 58:30:10:2, respectively.…”
Section: Methodsmentioning
confidence: 99%
“…For Merck formulations, LNP encapsulating mRNA were prepared by rapid precipitation process as previously described. 53 The lipid components of the LNP comprised an asymmetric ionizable amino lipid, 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC), cholesterol and poly(ethylene glycol)2000dimyristoylglycerol (PEG2000-DMG) in a molar ratio of 58:30:10:2, respectively. For formulations carried out by Moderna, LNPs were generated as described in, 34 and lipids were dissolved in ethanol at molar ratios of 50:10:38.5:1.5 (ionizable lipid: DSPC: cholesterol: PEG-lipid).…”
Section: Discussionmentioning
confidence: 99%